Digital processing of optical emission spectra of magnetron sputtering plasma system - Afanasіeva, I.A.; Afanasiev, S.N.; Azarenkov, N.A.; Bobkov, V.V.; Gritsyna, V.V.; Logachev, Yu.E.; Okseniuk, I.I.; Skrypnyk, A.A.; Shevchenko, D.I.; Chornous, V.M. (Вопросы атомной науки и техники, 2019)
To solve the actual problem of the analysis of the sputtered particles radiation during coating deposition in a magnetron sputtering system, a digital technique was proposed for processing the emission spectra of the discharge plasma. A graphic OSA application has been created, which allows obtaining qualitative and quantitative characteristics of the magnetron discharge plasma. The obtained information about the distribution of excited particles along the direction parallel to the axis of the magnetron discharge permits one to control the mode of the discharge operation and, as a consequence, the properties of the deposited coatings.